The characterisation of mcallisterite synthesised from bischofite via the hydrothermal method - Gurses, Pelin; Yildirim, Meral; Kipcak, Azmi Seyhun; Yuksel, Sureyya Aydin; Derun, Emek Moroydor; Piskin, Sabriye (IOS PRESS, 2015)
This study investigated the effects of reaction time and temperature on the hydrothermal synthesis and physical properties of mcallisterite [Mg-2(B6O7(OH)(6))(2)center dot 9(H2O)], a type of a magnesium borate. Different parameters that affect the final products were determined by various techniques including X-ray diffraction (XRD), Fourier transform infrared (FT-IR) and Raman spectra, Differential Thermal Analysis and Thermal Gravimetry (DTA/TG). The surface morphology of synthesized mcallisterite was investigated by Scanning Electron Microscope (SEM). B2O3 (boron oxide) content was determined through a gravimetric method of titration. Optical absorption characteristics of mcallisterite were investigated by UV-vis spectrometer and Picoammeter Voltage Source was used to measure electrical properties.
Keywords: Mcallisterite; optical properties; electrical properties; hydrothermal synthesis; magnesium borate; MAGNESIUM BORATE NANORODS; ROUTE; NANOWHISKERS; Chemistry